2020
DOI: 10.21037/atm.2020.02.148
|View full text |Cite
|
Sign up to set email alerts
|

Pre-clinical assessment of chimeric antigen receptor t cell therapy targeting CD19+ B cell malignancy

Abstract: Background: Autologous chimeric antigen receptor (CAR) T cell therapy is a promising therapeutic strategy for treating hematologic malignancies. A spectrum of serious complications caused by CAR-T cells has caught great attention. We developed a novel CAR against CD19 namely UWC19, consisting anti-CD19 single-chain variable fragment (scFv) hinged with 4-1BB and CD3z signaling domains. In this study, preclinical assessments of UWC19 were conducted to evaluate the safety and efficacy in vitro and in vivo. Method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 22 publications
1
7
0
Order By: Relevance
“…The amounts of CAR-CD19 T cells were chosen based on the clinical doses tested in the clinical trial for treating patients with ALL. This study is consistent with the previous findings that showed CARs increased the potency of the engineered T cells in a pre-clinical setting [ 36 – 40 ]. Nevertheless, further pre-clinical testing is required, including experiments in NOD SCID gamma mouse (NSG) animals, to ensure the dose and the in vivo activity of modified CAR T cells.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The amounts of CAR-CD19 T cells were chosen based on the clinical doses tested in the clinical trial for treating patients with ALL. This study is consistent with the previous findings that showed CARs increased the potency of the engineered T cells in a pre-clinical setting [ 36 – 40 ]. Nevertheless, further pre-clinical testing is required, including experiments in NOD SCID gamma mouse (NSG) animals, to ensure the dose and the in vivo activity of modified CAR T cells.…”
Section: Discussionsupporting
confidence: 93%
“…Therefore, a single dose of tumor cell line (Raji LUC/GFP) was injected into immunodeficient mice (C.B.17/Icr-scid/scidJcl) to create a model as close to the human disease as possible. The dose of the Raji cancer cell line (500,000 cells/mouse) was based on previously published data [ 36 ]. Administration of both the Raji cell line and CAR-CD19 T cells did not affect the body weight of the treated mice throughout the study period.…”
Section: Discussionmentioning
confidence: 99%
“…T cells transfected with HMEJ template, gRNAs and Cas9 were more efficiently engineered (52.4% ±5.16) than those transfected with HR template, gRNA and Cas9 (42.8% ±4. 43), but at a cost of a slightly lower viability (79.1% ±2.07 vs 73.1% ±4.25, respectively) ( Figure 2C&D ). We also compared HMEJ mediated integration to another previously reported HR-based integration strategy that uses a linear double stranded DNA template generated through PCR 12,14 .…”
Section: Hmej Allows For High Efficiency Targeted Non-viral Integration Of Large Cargomentioning
confidence: 93%
“…Specific pathogen-free female NODscid IL2Rgamma null (NSG) mice were purchased from Jackson Labs. Tumor challenge studies were performed using the Raji-luc cell line, a well-defined model of Burkitt Lymphoma used for testing CAR-T function 42,43 . Specifically, mice were implanted with 1x10 5 Raji-luc cells resuspended in 50% Matrigel (Corning) through a 100 µL intraperitoneal (IP) injection.…”
Section: In Vivo Car-t Therapy Experimentsmentioning
confidence: 99%
“…Anti-tumor effects of CD19-directed CAR T-cells against PCNSL have not only been demonstrated in vitro, but also in murine in vivo models [16,17]. Mulazzani et al designed an orthotopic PCNSL model by combining a chronic cranial window with two-photon intravital microscopy, allowing the repetitive visualization of brain tumor growth [16].…”
Section: Preclinical and Clinical Data 21 Preclinical Datamentioning
confidence: 99%